2020
DOI: 10.4070/kcj.2020.0158
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications of Novel Anti-Cancer Immunotherapy: Old Problems from New Agents?

Abstract: Many novel anti-cancer therapies have dramatically improved outcomes of various cancer patients. However, it also poses a risk for cardiovascular complications as well. For the novel anti-cancer agent with which physicians does not have enough clinical experiences to determine the characteristics of cardiovascular complications, it is important to assess risk factors for cardiotoxicity before starting anti-cancer therapy. High-risk patient should be consulted to cardiologist before initiating anti-cancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…10,18,19 The number of patients with prior malignancy needing HTx is also increasing due to increased numbers of cancer survivors and cardiotoxic cancer treatment. [12][13][14][15][16][17][18][19] Recent registry data from the United Network for Organ Sharing (UNOS) revealed that early survival of patients with PTM was poorer driven by increased mortality for patients with hematologic PTM, but mortality at 5 year of PTM was comparable between those with and without PTM. 23 However, detailed clinical characteristics and comprehensive outcomes including CAV, NF-MACE, ATR, ACR, and AMR have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,18,19 The number of patients with prior malignancy needing HTx is also increasing due to increased numbers of cancer survivors and cardiotoxic cancer treatment. [12][13][14][15][16][17][18][19] Recent registry data from the United Network for Organ Sharing (UNOS) revealed that early survival of patients with PTM was poorer driven by increased mortality for patients with hematologic PTM, but mortality at 5 year of PTM was comparable between those with and without PTM. 23 However, detailed clinical characteristics and comprehensive outcomes including CAV, NF-MACE, ATR, ACR, and AMR have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Aging population and improved cancer treatment have resulted in a growing number of cancer survivors. 10,18,19 The number of patients with prior malignancy needing HTx is also increasing due to increased numbers of cancer survivors and cardiotoxic cancer treatment. [12][13][14][15][16][17][18][19] Recent registry data from the United Network for Organ Sharing (UNOS) revealed that early survival of patients with PTM was poorer driven by increased mortality for patients with hematologic PTM, but mortality at 5 year of PTM was comparable between those with and without PTM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant advances in immunotherapies have been made in the treatment of malignancy. 52) 53) As malignancy remains the major limitation to long term longevity after solid organ transplant, 54) if immunotherapy used for treatment of malignancy can cross over and be used in maintenance immunosuppression post-transplant, there is hope that limited lifespan due to malignancy will be addressed.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, it has been documented that all of these factors collectively lead to congestive heart failure and sudden cardiac death. Table 1 summarizes the adverse cardiotoxic consequences of chemotherapy [ 114 ].…”
Section: Mode Of Cardiotoxicity Inductionmentioning
confidence: 99%